Complicity: Methodologies of power, politics and the ethics of knowledge production. (14th December 2022) - Hollin, Gregory; Williams, Ros
Abstract: In this collection we develop the concept of "complicity" as a means to understand how medical sociologists might be allied in unexpected or uncomfortable ways with dominant structures of power. After giving examples of complicity from our own research, we introduce existing scholarship on complicity, describing it as a concept that comes coupled with a sense of responsibility and that is related to, yet distinct from, a range of other terms including reflexivity, collusion, guilt, and shame. We also discuss how complicity has been described to occur at the level of the institution, within theoretical frameworks, and during mundane moments that we face on a day‐to‐day basis. Building on this review, we hypothesise that medical sociology – where access to fieldsites is often hard won, where "researching up" in medical and scientific institutions is common, and where our own work frequently concerns matters central to medical institutions themselves – is a discipline wherein mundane complicity is likely. Following this gathering exercise, we introduce the interventions that comprise this collection: interventions from a diversity of sociologists of health and illness who, perhaps for the first time in written form, account for how complicities of various kinds came to shape their work and how, with varying levels of success, they have sought redress. We close by offering some insight into the process of developing this collection, celebrating its successes while also acknowledging that many gaps and complicities remain.